A distributed leadership change process model for higher education. Issue 2 (4th March 2017) - Jones, Sandra; Harvey, Marina
ABSTRACT: The higher education sector operates in an increasingly complex global environment that is placing it under considerable stress and resulting in widespread change to the operating context and leadership of higher education institutions. The outcome has been the increased likelihood of conflict between academics and senior leaders, presaging the need for more engaged and broader approach to leadership. Based on empirical research into the Australian university sector, this paper contends that a distributed leadership (DL) approach is appropriate for the higher education sector and offers value for supporting effective change. In acknowledging the paradigm change needed to implement a DL approach successfully, the authors present a process model to underpin the shift from a leader-centric to a DL approach. The Sustainable Enabling and Evaluating Reflective DL change process model presents a synthesis of how a systemic change to DL in higher education can occur.